Tinjauan Terhadap Fenomena Pengemis Online Dengan Dikeluarkannya Surat Edaran Nomor 2 Tahun 2023 Oleh Menteri Sosial Republik Indonesia - Ni Wayan Dian Anggita Sari; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2024)
A new problem faced by society due to technological advances is the use of social media such as TikTok to beg online. This activity is carried out by utilizing virtual gifts on Tik Tok live streaming . Problem formulation: How is the law enforcement of the phenomenon of online begging with the issuance of Circular Letter Number 2 of 2023 by the Minister of Social Affairs of the Republic of Indonesia? What factors are an obstacle in law enforcement against online begging on social media? This research uses normative law type, with statutory, factual, and conceptual approaches. Minister of Social Affairs Circular Letter Number 2 of 2023 was released in response to the phenomenon of online begging. There is no specific legislation regulating online begging, but currently to stop it there is a regulation in the Criminal Code Article 504 concerning criminal sanctions for begging so that this sanction can stop online begging activities. Therefore, the government needs to accommodate the rules of online begging by forming special regulations related to this matter, as well as increasing the supervision of content on social media.